Identifying links between athletic identity and risk factors related to youth sport participation - Choudhury, M. Minnat; Erdman, Ashley L.; Stapleton, Emily; Gale, Emily; Ulman, Sophia (Frontiers in Psychology, 2024)
The development of identity formation occurs during adolescence through experiences, ideals and principle. With greater accessibility to sports, recent trends have shown increased rates of sports specialization over the past decade in youth athletes. Athletic identity measures the strength an individual is tied to the athlete role and can be formed in conjunction to adolescent identity formation. More specialized youth athletes may have stronger ties to their athletic identity during their adolescent identity formation period. Youth basketball athletes were surveyed on specialization levels and athletic identity via the Athletic Identity Measurement Scale (AIMS), including three submeasures: social identity, exclusivity, and negative affectivity. Participants showed stronger identification to social identity items and the weakest identification with exclusivity items. Athletes reporting more time spent playing their primary sport presented higher scores across all measures of athletic identity, and total athletic identity was stronger in athletes reporting specialization at an earlier age. Exclusivity and negative affectivity tended to increase with specialization level which may primarily be driven by specialized athletes choosing to quit non-primary sports. Athletic identity may be worth noting as a psychological indicator of potential risk of injury. The long-term goal of this work is to provide the research and clinical community a greater understanding of a potential psychosocial risk factor as youth athletes continue specializing and spending more time training in a singular sport.